Corrigendum to “Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage” [For. Ecol. Manage. 1 – May 27, 2026] - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Conversion of tropical peat swamp forest to oil palm plantations shifts prokaryotic beta diversity and reshapes the community structure, composition, and co-occurrence patterns of soil biota - Farhana Adilah Zahari; Sharon Yu Ling Lau; Meldon Fienberg Kelbin; Gaik Ee Lee; Umar Hussaini Tarmizi; Qiqian Wu; Xiangzhen Li; Lars Vesterdal; Jan Frouz; Chengming You; Amirah Alias; Kai Yue; et al. (Forest Ecology and Management, 2026)

Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Peak season soil GHG exchange after 23 years of ungulate exclusion in an old-growth temperate forest - Frederik Nygaard Philipsen; Joanne Alice O’Keeffe; Dries P.J. Kuijper; Marcin Churski; Stanisław Miścicki; Bogumiła Jędrzejewska; Jeppe Å. Kristensen; Elizabeth le Roux; Yue Cheng; Carsten W. Mueller; Lars Vesterdal; Klaus Steenberg Larsen; et al. (Agricultural and Forest Meteorology, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Global negative effects of fire on soil fauna communities vary with geographic factors and taxonomic groups - Dixin Chen; Xin Peng; Matthias C. Rillig; Lars Vesterdal; Yan Peng; Qiqian Wu; Zimin Li; Petr Heděnec; Yuexin Fan; Xiangyin Ni; Fuzhong Wu; Kai Yue (Plant and Soil, 2026)

Tree species identity, mycorrhizal associations, and land-use legacy shape soil protist diversity and community composition through litter quality and soil properties - Yves Theoneste Murindangabo; Fatimah Hashim; Nurul Shahida Redzuan; Haifeng Zheng; Yan Peng; Kai Yue; Jan Frouz; Flemming Ekelund; Lars Vesterdal; Petr Heděnec (Plant and Soil, 2026)

On the importance of soil texture for predicting future global soil respiration - Lucas Carvalho Gomes; Cássio Marques Moquedace; Ivan F. Souza; Ben Bond-Lamberty; Rodrigo Vargas; Lars Vesterdal; Gustavo V. Veloso; Marcio Rocha Francelino; Carlos E.G.R. Schaefer; Kendalynn A. Morris; Elpídio I. Fernandes-Filho (Science of The Total Environment, 2026)

Soil organic carbon sequestration over 50 years in resampled afforestation chronosequences on former cropland - Ming Yu; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Teresa G. Bárcena; Inger Kappel Schmidt; Per Gundersen; Ludovica D'Imperio; Carsten W. Mueller; Lars Vesterdal (Journal of Environmental Management, 2026)

Land use and soil texture drive shifts in communities of soil biota across natural and anthropogenic tropical ecosystems - Umar Hussaini Tarmizi; Farhana Adilah Zahari; Amirah Alias; Seng Chee Poh; Wei San Phang; Kai Yue; Yan Peng; Siti Norasikin Ismail; Xiangzhen Li; Haris Hafizal Abd Hamid; Mohamad Aqmal-Naser; Alexandre Soares Rosado; et al. (European Journal of Soil Biology, 2026)

Understory vegetation development along 60-year chronosequences of oak, beech, and Norway spruce - Davide Barsotti; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; Inger Kappel Schmidt (Forest Ecology and Management, 2026)

Structural diversity, tree species richness and biomass production in new forests on agricultural land - Yamina M. Rosas; Inger Kappel Schmidt; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; David Bille Byriel; Mathias Just Justesen; Davide Barsotti; Sebastian Kepfer-Rojas (Remote Sensing of Environment, 2025)

Soil microbes and nutrient inputs influence root nodulation and tree performance in Alnus glutinosa - Konstantinos Georgopoulos; T. Martijn Bezemer; Lars Vesterdal; Kaiyi Li; Léon de Nobel; Naksha Kasal; Sofia I.F. Gomes (Applied Soil Ecology, 2025)

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Ozone strengthens the ex vivo but weakens the in vivo pathway of the microbial carbon pump in poplar plantations - Haifeng Zheng; Lars Vesterdal; Evgenios Agathokleous; Xiangyang Yuan; Mingyue Yuan; Yansen Xu; Petr Heděnec; Bo Shang; Zhaozhong Feng; Johannes Rousk (Soil Biology and Biochemistry, 2024)

Perspectives: Resilient forests need joint forces for better inventorying and monitoring - Marco Ferretti; Arthur Gessler; Nathalie Cools; Stefan Fleck; Rossella Guerrieri; Tamara Jakovljević; Manuel Nicolas; Tiina M. Nieminen; Diana Pitar; Nenad Potočić; Stephan Raspe; Marcus Schaub; et al. (Forest Ecology and Management, 2024)

Tree species, mycorrhizal associations, and land-use history as drivers of cohesion in soil biota communities and microbe-fauna interactions - Petr Heděnec; Hanan Almahasheer; Qiang Lin; Yan Peng; Haifeng Zheng; David Pessanha Siqueira; Kai Yue; Umar Hussaini bin Tarmizi; Mohamad Aqmal-Naser; Siti Norasikin Ismail; Amirah Alias; Johannes Rousk; et al. (Forest Ecology and Management, 2024)

Global assessment of soil methanotroph abundances across biomes and climatic zones: The role of climate and soil properties - Petr Heděnec; Amirah Alias; Hanan Almahasheer; Chi Liu; Poh Seng Chee; Minjie Yao; Xiangzhen Li; Lars Vesterdal; Jan Frouz; Yongping Kou; Kai Yue (Applied Soil Ecology, 2024)

Mosses stimulate soil carbon and nitrogen accumulation during vegetation restoration in a humid subtropical area - Lumei Xiao; Wei Zhang; Peilei Hu; Lars Vesterdal; Jie Zhao; Li Tang; Dan Xiao; Kelin Wang (Soil Biology and Biochemistry, 2023)

Soil fauna effects on litter decomposition are better predicted by fauna communities within litterbags than by ambient soil fauna communities - Yan Peng; Lars Vesterdal; Josep Peñuelas; Guille Peguero; Qiqian Wu; Petr Heděnec; Kai Yue; Fuzhong Wu (Plant and Soil, 2023)

Litter chemistry of common European tree species drives the feeding preference and consumption rate of soil invertebrates, and shapes the diversity and structure of gut and faecal microbiomes - Petr Heděnec; Haifeng Zheng; David Pessanha Siqueira; Yan Peng; Inger Kappel Schmidt; Tobias Guldberg Frøslev; Rasmus Kjøller; Huan Li; Jan Frouz; Lars Vesterdal (Soil Biology and Biochemistry, 2023)

Tree species traits and mycorrhizal association shape soil microbial communities via litter quality and species mediated soil properties - Petr Heděnec; Haifeng Zheng; David Pessanha Siqueira; Qiang Lin; Yan Peng; Inger Kappel Schmidt; Tobias Guldberg Frøslev; Rasmus Kjøller; Johannes Rousk; Lars Vesterdal (Forest Ecology and Management, 2023)

Responses of soil fauna communities to the individual and combined effects of multiple global change factors - Yan Peng; Josep Peñuelas; Lars Vesterdal; Kai Yue; Guille Peguero; Dario A. Fornara; Petr Heděnec; Christina Steffens; Fuzhong Wu (Ecology Letters, 2022)
Soil fauna plays a key role in regulating biogeochemical cycles, but how multiple global change factors (GCFs) may affect faunal communities remains poorly studied. We conducted a meta‐analysis using 1154 observations to evaluate the individual and combined effects of elevated CO 2 , nitrogen (N) addition, warming, increased rainfall and drought on soil fauna density and diversity. Here we show that, overall, individual and combined effects of GCFs had negligible effects on soil fauna density and diversity, except that density was negatively affected by drought (−27.4%) and positively affected by increased rainfall individually (+24.9%) and in combination with N addition (+67.3%) or warming (+70.4%). GCF effects varied among taxonomic groups both in magnitude and direction. Variables such as latitude, elevation and experimental setting significantly impacted both individual and combined effects. Our results suggest that soil fauna density is affected by changed rainfall regimes, while diversity is resistant against individual and combined effects of multiple GCFs.

Effects of Litter Quality Diminish and Effects of Vegetation Type Develop During Litter Decomposition of Two Shrub Species in an Alpine Treeline Ecotone - Haifeng Zheng; Yamei Chen; Yang Liu; Petr Heděnec; Yan Peng; Zhenfeng Xu; Bo Tan; Li Zhang; Li Guo; Lifeng Wang; Lars Vesterdal (Ecosystems, 2021)

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Kai Yue; Yan Peng; Dario A. Fornara; Koenraad Van Meerbeek; Lars Vesterdal; Wanqin Yang; Changhui Peng; Bo Tan; Wei Zhou; Zhenfeng Xu; Xiangyin Ni; Li Zhang; et al. (Global Ecology and Biogeography, 2019)
Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.

The response of soil solution chemistry in European forests to decreasing acid deposition - James Johnson; Elisabeth Graf Pannatier; Stefano Carnicelli; Guia Cecchini; Nicholas Clarke; Nathalie Cools; Karin Hansen; Henning Meesenburg; Tiina M. Nieminen; Gunilla Pihl‐Karlsson; Hugues Titeux; Elena Vanguelova; et al. (Global Change Biology, 2018)
Acid deposition arising from sulphur (S) and nitrogen (N) emissions from fossil fuel combustion and agriculture has contributed to the acidification of terrestrial ecosystems in many regions globally. However, in Europe and North America, S deposition has greatly decreased in recent decades due to emissions controls. In this study, we assessed the response of soil solution chemistry in mineral horizons of European forests to these changes. Trends in pH , acid neutralizing capacity ( ANC ), major ions, total aluminium (Al tot ) and dissolved organic carbon were determined for the period 1995–2012. Plots with at least 10 years of observations from the ICP Forests monitoring network were used. Trends were assessed for the upper mineral soil (10–20 cm, 104 plots) and subsoil (40–80 cm, 162 plots). There was a large decrease in the concentration of sulphate ( ) in soil solution; over a 10‐year period (2000–2010), decreased by 52% at 10–20 cm and 40% at 40–80 cm. Nitrate was unchanged at 10–20 cm but decreased at 40–80 cm. The decrease in acid anions was accompanied by a large and significant decrease in the concentration of the nutrient base cations: calcium, magnesium and potassium (Bc = Ca 2+ + Mg 2+ + K + ) and Al tot over the entire dataset. The response of soil solution acidity was nonuniform. At 10–20 cm, ANC increased in acid‐sensitive soils (base saturation ≤10%) indicating a recovery, but ANC decreased in soils with base saturation >10%. At 40–80 cm, ANC remained unchanged in acid‐sensitive soils (base saturation ≤20%, ≤ 4.5) and decreased in better‐buffered soils (base saturation >20%, > 4.5). In addition, the molar ratio of Bc to Al tot either did not change or decreased. The results suggest a long‐time lag between emission abatement and changes in soil solution acidity and underline the importance of long‐term monitoring in evaluating ecosystem response to decreases in deposition.

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Is Tree Species Diversity or Species Identity the More Important Driver of Soil Carbon Stocks, C/N Ratio, and pH? - Seid Muhie Dawud; Karsten Raulund-Rasmussen; Timo Domisch; Leena Finér; Bogdan Jaroszewicz; Lars Vesterdal (Ecosystems, 2016)

Does species richness affect fine root biomass and production in young forest plantations? - Timo Domisch; Leena Finér; Seid Muhie Dawud; Lars Vesterdal; Karsten Raulund-Rasmussen (Oecologia, 2015)

Effects of forest expansion on mountain grassland: changes within soil organic carbon fractions - Claudia Guidi; Jakob Magid; Mirco Rodeghiero; Damiano Gianelle; Lars Vesterdal (Plant and Soil, 2014)

Afforestation effects on SOC in former cropland: oak and spruce chronosequences resampled after 13 years - Teresa G. Bárcena; Per Gundersen; Lars Vesterdal (Global Change Biology, 2014)
Chronosequences are commonly used to assess soil organic carbon ( SOC ) sequestration after land‐use change, but SOC dynamics predicted by this space‐for‐time substitution approach have rarely been validated by resampling. We conducted a combined chronosequence/resampling study in a former cropland area (Vestskoven) afforested with oak ( Quercus robur ) and Norway spruce ( Picea abies ) over the past 40 years. The aims of this study were (i) to compare present and previous chronosequence trends in forest floor and top mineral soil (0–25 cm) C stocks; (ii) to compare chronosequence estimates with current rates of C stock change based on resampling at the stand level; (iii) to estimate SOC changes in the subsoil (25–50 cm); and (iv) to assess the influence of two tree species on SOC dynamics. The two chronosequence trajectories for forest floor C stocks revealed consistently higher rates of C sequestration in spruce than oak. The chronosequence trajectory was validated by resampling and current rates of forest floor C sequestration decreased with stand age. Chronosequence trends in topsoil SOC in 2011 did not differ significantly from those reported in 1998, however, there was a shift from a negative rate (1998: −0.3 Mg C ha −1 yr −1 ) to no change in 2011. In contrast SOC stocks in the subsoil increased with stand age, however, not significantly ( P = 0.1), suggesting different C dynamics in and below the former plough layer. Current rates of C change estimated by repeated sampling decreased with stand age in forest floors but increased in the topsoil. The contrasting temporal change in forest floor and mineral soil C sequestration rates indicate a shift in C source‐sink strength after approximately 40 years. We conclude that afforestation of former cropland within the temperate region may induce soil C loss during the first decades followed by a recovery phase of yet unknown duration.

The natural abundance of 15N in litter and soil profiles under six temperate tree species: N cycling depends on tree species traits and site fertility - Ingeborg Callesen; Lars Ola Nilsson; Inger Kappel Schmidt; Lars Vesterdal; Per Ambus; Jesper Riis Christiansen; Peter Högberg; Per Gundersen (Plant and Soil, 2013)

Four decades of post-agricultural forest development have caused major redistributions of soil phosphorus fractions - An De Schrijver; Lars Vesterdal; Karin Hansen; Pieter De Frenne; Laurent Augusto; David Ludovick Achat; Jeroen Staelens; Lander Baeten; Luc De Keersmaeker; Stefaan De Neve; Kris Verheyen (Oecologia, 2012)

Tree species traits cause divergence in soil acidification during four decades of postagricultural forest development - An de Schrijver; Pieter de Frenne; Jeroen Staelens; Gorik Verstraeten; Bart Muys; Lars Vesterdal; Karen Wuyts; Lotte van Nevel; Stephanie Schelfhout; Stefaan de Neve; Kris Verheyen (Global Change Biology, 2012)
A change in land use from agriculture to forest generally increases soil acidity. However, it remains unclear to what extent plant traits can enhance or mitigate soil acidification caused by atmospheric deposition. Soil acidification is detrimental for the survival of many species. An in‐depth understanding of tree species‐specific effects on soil acidification is therefore crucial, particularly in view of the predicted global increases in acidifying nitrogen ( N ) deposition. Here, we report soil acidification rates in a chronosequence of broadleaved deciduous forests planted on former arable land in Belgium. This region receives one of the highest loads of potentially acidifying atmospheric deposition in Europe, which allowed us to study a ‘worst case scenario’. We show that less than four decades of forest development caused significant soil acidification. Atmospheric deposition undoubtedly and unequivocally drives postagricultural forests towards more acidic conditions, but the rate of soil acidification is also determined by the tree species‐specific leaf litter quality and litter decomposition rates. We propose that the intrinsic differences in leaf litter quality among tree species create fundamentally different nutrient cycles within the ecosystem, both directly through the chemical composition of the litter and indirectly through its effects on the size and composition of earthworm communities. Poor leaf litter quality contributes to the absence of a burrowing earthworm community, which retards leaf litter decomposition and, consequently, results in forest‐floor build‐up and soil acidification. Also nutrient uptake and N 2 fixation are causing soil acidification, but were found to be less important. Our results highlight the fact that tree species‐specific traits significantly influence the magnitude of human pollution‐induced soil acidification.

Role of six European tree species and land‐use legacy for nitrogen and water budgets in forests - JESPER RIIS CHRISTIANSEN; LARS VESTERDAL; INGEBORG CALLESEN; BO ELBERLING; INGER KAPPEL SCHMIDT; PER GUNDERSEN (Global Change Biology, 2010)
Water and nutrient fluxes for single stands of different tree species have been reported in numerous studies, but comparative studies of nutrient and hydrological budgets of common European deciduous tree species are rare. Annual fluxes of water and inorganic nitrogen (N) were established in a 30‐year‐old common garden design with stands of common ash ( Fraxinus excelsior ), European beech ( Fagus sylvatica L.), pedunculate oak ( Quercus robur ), small‐leaved lime ( Tilia cordata Mill.), sycamore maple ( Acer pseudoplatanus ) and Norway spruce ( Picea abies [L.] Karst .) replicated at two sites in Denmark, Mattrup and Vallø during 2 years. Mean annual percolation below the root zone (mm yr −1 ±SE, n =4) ranked in the following order: maple (351±38)>lime (284±32), oak (271±25), beech (257±30), ash (307±69)≫ spruce (75±24). There were few significant tree species effects on N fluxes. However, the annual mean N throughfall flux (kg N ha −1 yr −1 ±SE, n =4) for spruce (28±2) was significantly larger than for maple (12±1), beech (11±1) and oak (9±1) stands but not different from that of lime (15±3). Ash had a low mean annual inorganic N throughfall deposition of 9.1 kg ha −1 , but was only present at Mattrup. Annual mean of inorganic N leaching (kg ha −1 yr −1 ±SE, n =4) did not differ significantly between species despite of contrasting tree species mean values; beech (25±9)>oak (16±10), spruce (15±8), lime (14±8)≫ maple (1.9±1), ash (2.0±1). The two sites had similar throughfall N fluxes, whereas the annual leaching of N was significantly higher at Mattrup than at Vallø. Accordingly, the sites differed in soil properties in relation to rates and dynamics of N cycling. We conclude that tree species affect the N cycle differently but the legacy of land use exerted a dominant control on the N cycle within the short‐term perspective (30 years) of these stands.

Are Indicators for Critical Load Exceedance Related to Forest Condition? - Karin Hansen; Lars Vesterdal; Annemarie Bastrup-Birk; Jørgen Bille-Hansen (Water, Air, & Soil Pollution, 2007)

Nitrate leaching from three afforestation chronosequences on former arable land in Denmark - KARIN HANSEN; LARS ROSENQVIST; LARS VESTERDAL; PER GUNDERSEN (Global Change Biology, 2007)
In regions dominated by agricultural activities, nitrogen (N) is recognized as a major pollutant in aquatic environments. In north‐western Europe, afforestation of agricultural land is part of a strategy to improve water quality. In Denmark, former arable land has been afforested during the past 40–50 years. This study evaluated the effect of afforestation of former arable land on nitrate leaching, based on three afforestation chronosequences. Precipitation, canopy throughfall and soil water were collected and soil moisture was monitored at two Danish locations, Vestskoven (nutrient‐rich, medium deposition) and Gejlvang (nutrient‐poor, high deposition). Afforestation was performed using Norway spruce [ Picea abies (Karst.) L.] and common oak ( Quercus robur L.) at Vestskoven and Norway spruce at Gejlvang. The results suggest that afforestation of former arable land initially leads to lower nitrate leaching than that occurring under the former agricultural land use, and largely below the standard of 50 mg NO − 3 L −1 for groundwater to be utilized as drinking water. Nitrate concentrations became almost negligible in forest stands of 5–20 years of age. However, after canopy closure (>20 years) nitrate concentrations below the root zone and nitrate leaching tended to increase. This was attributed to increased N deposition with increasing canopy development and decreased N demand once the most N‐rich biomass compartments had been built up. Nitrate leaching started to increase at a throughfall deposition level of about 10 kg N ha −1 yr −1 . Compared with nutrient‐poor sandy soils, nutrient‐rich clayey soils appeared more vulnerable to disturbance of the N cycle and to increased N deposition, leading to N saturation and enhanced nitrate leaching. In approximately the first 35 years after afforestation, nitrate leaching below the root zone was generally higher below oak than below Norway spruce.

Gap formation in Danish beech (Fagus sylvatica) forests of low management intensity: soil moisture and nitrate in soil solution - Eva Ritter; Lars Vesterdal (European Journal of Forest Research, 2006)

Changes in soil properties after afforestation of former intensively managed soils with oak and Norway spruce - Eva Ritter; Lars Vesterdal; Per Gundersen (Plant and Soil, 2003)